A NEW SPECIES OF KRYPTOBAATAR (MULTITUBERCULATA): THE FIRST LATE CRETACEOUS MAMMAL FROM INNER MONGOLIA (P. R. CHINA) - Smith T.; Guo D.-Y.; Sun Y. (My University, 2001)
Multituberculates are the best represented mammals of the Late Cretaceous in Asia and most of them are from Outer Mongolia. The djadochtatherioidean multituberculate Kryptobaatar mandahuensis n. sp. is described on the basis of two skulls from the Upper Cretaceous locality of Bayan Mandahu (Inner Mongolia, People's Republic of China). The main characters that differentiate it from the type species K. dashzevegi Kielanjaworowska, 1970 are: The base of the zygomatic arch situated at the level of the anterior root of the P4 and the narrow anterior extent of the orbit, the "V" shape of the palatomaxillary suture between the two major palatine foramina, the high and thick part of the dentary under the mandibular diastema, the long and low part of the dentary under the mandibular notch, the anteroposteriorly short coronoid process, the presence of 5 cusps on the middle row of M1 and on the labial row of m1, the long p4, the high ratio p4:m1 length, and the robust i1. The presence of this species in Inner Mongolia extends the palaeogeographical distribution area of the djadochtatherioideans to the southern part of the Gobi Basin. Nevertheless, morphological differences between K. mandahuensis from Inner Mongolia and K. dashzevegi from Outer Mongolia suggest a palaeogeographical isolation within the Djadochtatherioidea group during the Campanian.
Keywords: Late Cretaceous; Mammals; Multituberculata; Djadochtatherioidea; Inner Mongolia; Мезозой::Меловая; Mesozoic::Cretaceous